Organizational Citizenship Behaviors: A Critical Review of the Theoretical and Empirical Literature and Suggestions for Future Research - Podsakoff, Philip M.; MacKenzie, Scott B.; Paine, Julie Beth; Bachrach, Daniel G. (Journal of Management, 2000)
The rapid growth of research on organizational citizenship behaviors (OCBs) has resulted in some conceptual confusion about the nature of the construct, and made it difficult for all but the most avid readers to keep up with developments in this domain. This paper critically examines the literature on organizational citizenship behavior and other, related constructs. More specifically, it: (a) explores the conceptual similarities and differences between the various forms of “citizenship” behavior constructs identified in the literature; (b) summarizes the empirical findings of both the antecedents and consequences of OCBs; and (c) identifies several interesting directions for future research.